РАЗРАБОТКА, РЕАЛИЗАЦИЯ И ЭКСПЕРИМЕНТАЛЬНОЕ ВЫЯВЛЕНИЕ ОШИБОК АЛГОРИТМОВ АДАПТИВНОЙ ФИЛЬТРАЦИИ В РЕЖИМЕ РЕАЛЬНОГО ВРЕМЕНИ В СИСТЕМАХ АКТИВНОГО ШУМОВОГО КОНТРОЛЯ - Зыков, Александр Михайлович (Интеллектуальные системы в производстве, 2015)
The main issues of designing the algorithms for digital signal processing in systems of active noise cancellation are considered. The paper presents the main results of the design, implementation and analysis of performance and detection of errors of the developed digital filters for active noise control systems in real time mode. The work was performed as part of the grant RFBR No № 14-07-31100\14 (mol_a).